The mechanism of andrographolide as antiatherogenic agent against atherosclerosis induced by porphyromonas gingivalis - an experimental study in rabbit / Rami Albatran - Albatran, Rami (Institute of Graduate Studies, UiTM, 2014)
Atherosclerosis has been widely accepted as an inflammatory disease of the vascular system. An association between atherosclerosis and Porphyromonas gingivalis (Pg), a major periodontopathogen, has been shown. The aim of the present study was to evaluate the mechanism of the anti-atherogenic effect of andrographolide (AND) on atherosclerosis induced by Pg in male white New Zealand rabbits.